A Step towards Sustainability of Qualitative Life in Juvenile Delinquents - Shailja D., Gaytri Tiwari, Ashwani Kumar Verma (Archives of Current Research International, 2024)
Juvenile delinquency is a complex social problem that affects the individual in all strata of society. It implies the involvement of juveniles in activities which is illegal by the law. These antisocial acts of juveniles can be due to an inappropriate upbringing, lack of emotional support and material deprivation of family. Therefore, this study aimed to look at quality of life and psychological health among juvenile delinquents in Udaipur. Subjects for this study were 30 juvenile delinquents using a purposive sampling technique, 15 boys and 15 girls between 14-18 years of age who were undergoing institutionalized in two rehabilitation centers. Quality of life scale was used to measure quality of life and self-structured questionnaire was used to assess psychological health. The Pearson correlation showed that there was positive correlation between psychological health and all the six dimensions of psychological health: spirituality/religion/personal beliefs and thinking/learning/memory and concentration. In the light of research findings, we recommend a strong need to educate every child this may further help to eradicate poverty. There is also a strong need on the part of parents to keep check on their children in this way they will restrain them to develop delinquent personality.